African Cultural Imaginaries and (Post-)Development Thought. - Kopf, Martina (Journal of African Cultural Studies, 2022)
In this special issue, we read discourses and practices of development in Africa through the lens of African literature and cultural imaginations. Neither in development theory as academic field, nor in the development agendas of governments and international organisations, has the knowledge expressed in literature and oral culture in Africa been seriously integrated. Indeed, in Africa in particular "culture" has often been constructed as an obstacle and as backward in the discourse on African development (see Odhiambo [10]). The article thus contests an "emerging, but synthetic narrative of precarious woman's land rights in Acholi" in Western-oriented feminist discourse and male-centred traditionalist discourse alike and brings a pragmatic African feminist approach to a topic that, as Okot shows, is often misunderstood or wilfully misinterpreted.